Memory Politics, Identity and Conflict Historical Memory as a Variable - Wang, Zheng (Memory Politics and Transitional Justice, 2018)
This book focuses on the methodology of research on historical memory and contributes to theoretical discussions concerning the use of historical memory as a variable to explain political action and social movement. The chapters of the book conceptualize the relationship between historical memory and national identity formation, perceptions, and policy-making. The author particularly analyses how contested memory and the related social discourse can lead to nationalism and international conflict. Based on theories and research from multiple fields of studies, this book proposes a series of analytic frameworks for the purpose of conceptualizing the functions of historical memory. These analytic frameworks can help categorize, measure, and subsequently demonstrate the effects of historical memory. This book also discusses how to use public opinion polls, textbooks, important texts and documents, monuments and memory sites for conducting research to examine the functions of historical memory. Zheng Wang is the Director of the Center for Peace and Conflict Studies and Professor in the School of Diplomacy and International Relations at Seton Hall University, USA. He is also a Carnegie Fellow at New America and a Global Fellow at the Woodrow Wilson International Center for Scholars. Wang is the author of Never Forget National Humiliation: Historic Memory in Chinese Politics and Foreign Relations, which received the International Studies Association's Yale H. Ferguson Award.